EMTP-ATP Draw Based Model for Performance Evaluation of Onsite Partial Discharge Measurement for Underground XLPE Cables - Atsever, M. B.; Deveci, U.; Yuzgulec, S.; Mesci, N.; Yilmaz, S. C.; Yarkan, S.; Hocaoglu, M. H. (IEEE, 2024)
Underground cable monitoring is a critical task for DSOs. During the operation or commissioning, the insulation of the underground cable may be deteriorated. Thus, PDs may occur through the insulation layers. It is wise to detect and locate the PDs before severe insulation breakdowns. Comprehensive EMPT-ATP Draw based parametric analysis have been carried out in a representative cable feeder. The simulation results clearly show that the location of the PD can be detected with high accuracy using EMPT-ATP Draw model. With this motivation the real distribution network and HFCT are modeled. On-site PD measurement results and EMPT-ATP Draw simulation results are compared. Results obtained from a real on-site measurements and EMPT-ATP Draw model were found to be similar.
3rd International Conference on Power Systems and Electrical Technology -- AUG 05-08, 2024 -- JAPAN
Keywords: partial discharge; cable; insulation; preventive protection; EMTP; onsite measurement